Predictive validity and efficiency of ongoing visual‐inspection criteria for interpreting functional analyses. Issue 2 (12th March 2018) - Saini, Valdeep; Fisher, Wayne W.; Retzlaff, Billie J.
Abstract : Prior research has evaluated the reliability and validity of structured criteria for visually inspecting functional‐analysis (FA) results on a post‐hoc basis, after completion of the FA (i.e., post‐hoc visual inspection [PHVI]; e.g., Hagopian et al., 1997). However, most behavior analysts inspect FAs using ongoing visual inspection (OVI) as the FA is implemented, and the validity of applying structured criteria during OVI remains unknown. In this investigation, we evaluated the predictive validity and efficiency of applying structured criteria on an ongoing basis by comparing the interim interpretations produced through OVI with (a) the final interpretations produced by PHVI, (b) the authors' post‐hoc interpretations (PHAI) reported in the research studies, and (c) the consensus interpretations of these two post‐hoc analyses. Ongoing visual inspection predicted the results of PHVI and the consensus interpretations with a very high degree of accuracy, and PHAI with a reasonably high degree of accuracy. Furthermore, the PHVI and PHAI results involved 32 FA sessions, on average, whereas the OVI required only 19 FA sessions to accurately identify the function(s) of destructive behavior (i.e., a 41% increase in efficiency). We discuss these findings relative to other methods designed to increase the accuracy and efficiency of FAs.